Implementation of language politeness in online learning as an effort to optimise character education of pre-service elementary school teachers - Nugraheti Sismulyasih SB; Panca Dewi Purwati; Moh. Farizqo Irvan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The issue that requires serious attention is the use of language through mobile phones, which often neglects aspects of politeness in communication. This study aims to (1) examine the use of language politeness among PGSD UNNES student teachers in their interactions with lecturers through short messages and direct communication in online learning, (2) identify violations of the principles of language politeness in short message communication, and (3) develop a language politeness program in online learning as an effort to optimise character education. The research employed the research and development (R&D) method using the Borg & Gall model, with PGSD UNNES students as the subjects. Data were collected through interviews, observations, questionnaires, rating scales, tests, and performance tasks, and were analysed both descriptively and using the n-gain test. The validation results indicated that the language politeness handbook was deemed feasible to use (media expert score: 57 out of a total score of 75; material expert score: 73 out of a total score of 75). The effectiveness test yielded an n-gain of 0.7 (high category), demonstrating that the handbook effectively improves the language politeness of pre-service elementary school teachers and significantly increases students' understanding and application of polite language after the intervention.